Intra-abdominal Pressure Screening of Horses With Colic - de Paula, Vanessa B. [UNESP]; Canola, Paulo A. [UNESP]; Rivera, Gabriela G. [UNESP]; Bonacin, Yuri S. [UNESP]; Del Rio, Lara A.; Canola, Júlio C. [UNESP]; Ferraudo, Antônio S. [UNESP] (Elsevier, 2020)
The objective of this study was to evaluate changes in intra-abdominal pressure (IAP) in horses with colic by associating the underlying etiologies with directly acquired IAP values and survival rate. This is a 2-year cohort study (2014–2016). Horses with clinical signs of colic were admitted to the veterinary teaching hospital during the period 2014–2016. Twenty-eight horses, of different breeds, males (stallions and geldings) and females, aged between 2 and 20 years, and weighing from 300 to 450 kg presenting with clinical signs of colic, were included in the study. IAP was directly acquired at the right flank (standing under sedation) and at the linea alba (supine position under general anesthesia). Twenty IAP measurements were recorded at end expiration for each recording site. IAP values >0.0 mmHg, obtained at the upper right flank in the standing position, were associated with surgical treatment (P < .05). In these cases, signs of colic were associated with strangulated obstructions of the large colon, and a greater likelihood of death as a result of colic (P < .001). Intra-abdominal pressure varied considerably in horses with colic, even for the same underlying etiologies. Horses with colic related to strangulating obstructions of the large intestine had IAP >.0 mmHg, at the upper right flank. These horses were also considerably more likely to require surgical intervention (P < .05) and death/euthanasia was more likely in this group of horses (P < .001).
Keywords: Abdominal perfusion pressure; Acute abdomen; Celiotomy; Dorsal recumbency; Equine